GROWTH AND YIELD INDICES OF CASSAVA (MANIHOT UTILISSIMA) AND SOIL PHYSICO-CHEMICAL PROPERTIES AS AFFECTED BY DIFFERENT TRADITIONAL TILLAGE PRACTICES IN A HUMID ENVIRONMENT - ENUJEKE, Emmanuel Chukudinife; EGBUCHUA, Collins (International Journal of Research -GRANTHAALAYAH, 2021)
The study was conducted to assess the effects of traditional tillage practices namely No-till, Ridge-till and Mound-till, on cassava growth parameters and soil physico-chemical properties. It was a factorial experiment laid out in a randomised complete block design replicated 3-times. The factors were the 3-tillage methods and cassava plant as a test crop. Data collected on soil properties include the particle size distribution, soil bulk density, soil water content, hydraulic conductivity, soil pH, soil organic carbon, total nitrogen, available phosphorus and exchangeable bases, while data collected on plant growth and yield indices include; plant height, stem girth, number of leaves, number of tubers, tuber length and weight of tubers. The data were collected at 2, 4, 6, 8, 10 and 12 months but cumulated at 12 months after planting. The data were subjected to analysis of variance and relationship between cassava tuber yield and some soil properties measured. Results of the study showed that there was no significant difference between Ridge and Mound-till. The Ridge-till and Mound-till systems significantly influenced plant height, stem girth, number of leaves, tuber weight and total yield of cassava than No-till system, hence were recommended of increased yield of cassava in the study area.